Pituitary apoplexy can mimic acute meningoencephalitis or subarachnoid haemorrhage - Sadek, Ahmed-Ramadan (Springer, 2011)
Pituitary apoplexy is an uncommon but life-threatening condition that is often overlooked and underdiagnosed. We report a 45-year-old man who presented to our emergency department with a sudden onset headache, acute confusion, signs of meningeal irritation and ophthalmoplegia. An initial diagnosis of acute meningoencephalitis was made, which was amended to pituitary apoplexy following thorough investigation within the emergency department. A 45-year-old man was brought to our emergency department by ambulance with a history of sudden onset of frontal headache and acute confusion. His wife provided the history. There was no significant past medical history of diabetes, hypertension, recent travel abroad, exposure to sick contacts, involvement in outdoor pursuits such as hiking/cave diving, or trauma. He worked in a bank and had been well until 24 h prior to the onset of sudden headache, which was gradually worsening in nature and associated with increasing confusion. The patient's wife reported that he had neither experienced any fevers, night sweats, or coryzal symptoms nor received any recent vaccinations. He was not on any regular medications. He was a non-smoker and occasionally consumed alcohol. There was no significant family history. On examination in the ED, his temperature was 37.6°C, his pulse was 110/min, and he was normotensive and normoglycaemic. A macular blanching rash was noted over the patient's trunk. The patient was disoriented to time and place. Neurological examination revealed reduced GCS (11/15-E3, M6, V2), marked neck stiffness, a positive Kernig's sign and a right sixth nerve palsy. A provisional diagnosis of acute meningoencephalitis was made and the patient was started on a course of intravenous antibiotics with benzyl penicillin 1.2 g, cefotaxime 2 g and acyclovir 750 mg. Baseline blood investigations revealed hyponatraemia (122 mmol/l), a white-cell count of 11 × 10(9)/l and a C-reactive protein > 250. Due to the sudden onset of the symptoms and lack of prodrome, an urgent CT head scan was performed to rule out a cerebrovascular event. The scan demonstrated an enlarged pituitary gland (3 cm in diameter) with impingement of the optic chiasm. The centre of the enlarged pituitary gland was noted to be hypodense in comparison to its periphery, which was consistent with a diagnosis of pituitary apoplexy. A subsequent MRI confirmed the diagnosis (Figure 1) of an enlarged sella containing abnormal soft tissue with increased signal intensity suggestive of haemorrhage (Figure 1A). Post-MRI a lumbar puncture was performed revealing glucose 3.4 mmol/l, protein 1.0 g/l, red cells of 53/mm(3 )and white cells of 174/mm(3 )with predominant neutrophilia. No organisms were seen, and CSF cultures and HSV DNA tests were found to be negative. Endocrinological investigations demonstrated low concentrations of thyroid hormones [TSH: 0.14 mIu/l (0.35-5.5 mlU/l), FT3: 1.1 nmol/l (1.2-3.0 nmol/l), FT(4): 9.6 pmol/l (8-22 pmol/l)], gonadal hormones (LH: < 1 u/l) and prolactin: 16 u/l (<450 u/l). Serum FSH was 2.9 u/l (0.8-11.5 u/L) and cortisol 575 nmol/l (450-700 nmol/l). The patient was treated for hypopituitarism based on clinical and radiological findings with intravenous fluids, hydrocortisone (100 mg) and thyroxine (50 μg) as loading doses in the ED. Within 24 h of commencement of therapy the patient's GCS rose to 15, and within 48 h there was marked improvement in the right sixth cranial nerve palsy. Formal visual field assessment demonstrated temporal visual field loss in the left eye. The patient was discharged to his usual residence a week later and follow-up was organised with both the endocrinologists and ophthalmologists. Follow-up MRI demonstrated that there was no significant change in either size or signal characteristics of the pituitary fossa mass (Figure 1B).